Post-feeding hyperammonaemia in patients with transjugular intrahepatic portosystemic shunt and liver cirrhosis: role of small intestinal ammonia release and route of nutrient administration. Issue 6 (1st June 2000) - Plauth, M; Roske, A-E; Romaniuk, P; Roth, E; Ziebig, R; Lochs, H
Abstract : BACKGROUND: Hyperammonaemia is a pathogenetic factor for hepatic encephalopathy that may be augmented after a transjugular intrahepatic portosystemic shunt (TIPS). Experimental data suggest that hyperammonaemia may be caused to a large extent by metabolism of small intestinal enterocytes rather than colonic bacteria. AIMS: To evaluate if ammonia release and glutamine metabolism by small intestinal mucosa contribute to hyperammonaemia in vivo in patients with liver cirrhosis. METHODS: Using TIPS to examine mesenteric venous blood, we measured mesenteric venous-arterial concentration differences in ammonia and glutamine in patients with liver cirrhosis before, during, and after enteral (n=8) or parenteral (n=8) isonitrogenous infusion of a glutamine containing amino acid solution. RESULTS: During enteral nutrient infusion, ammonia release increased rapidly compared with the post-absorptive state (65 (58–73) v 107 (95–119) μmol/l after 15 min; mean (95% confidence interval)) in contrast with parenteral infusion (50 (41–59) v 62 (47–77) μmol/l). This resulted in a higher portal ammonia load (29 (21–36) v 14 (8–21) mmol/l/240 minutes) and a higher degree of systemic hyperammonaemia (14 (11–17) v 9 (6–12) mmol/l/240 minutes) during enteral than parenteral infusion. The mesenteric venous-arterial concentration difference in glutamine changed from net uptake to release at the end of the enteral infusion period (−100 (−58 to −141) v 31 (−47–110) μmol/l) with no change during parenteral nutrition. CONCLUSIONS: These data suggest that small intestinal metabolism contributes to post-feeding hyperammonaemia in patients with cirrhosis. When artificial nutrition is required, parenteral nutrition may be superior to enteral nutrition in patients with portosystemic shunting because of the lower degree of systemic hyperammonaemia.